On Music, Torture and Detention: Reflections on Issues of Research and Discipline - Anna Papaeti (Transposition, 2020)
This essay explores the late engagement of music research with the long-standing yet overlooked association between music, violence and terror. In mapping this new field, it seeks to understand this latency as a disciplinary trauma. It examines music’s integral role in new technologies of terror emerging during the Cold War, the cultural biases that have turned it into an elusive means of torture, and the effects stemming from the overshadowing of its damaging potential. Focusing on the notion of witnessing, it highlights the need for more nuanced soundscapes of detention that explore the entanglement of negative and positive uses of music as they are imposed from above and reclaimed from below.